Doing No Harm and Getting It Right: Guidelines for Ethical Research with Immigrant Communities. Issue 141 (3rd September 2013) - Hernández, María G.; Nguyen, Jacqueline; Casanova, Saskias; Suárez‐Orozco, Carola; Saetermoe, Carrie L.
Abstract: This chapter provides a guide to research logistics and ethics in studying immigrant families. The authors outline major pragmatic issues in research design and data collection to which all scholars must attend, although current practices often do not respond to the idiosyncratic issues related to vulnerable immigrant populations (e.g., undocumented immigrants). The chapter presents vital procedures to ensure both the protection of research participants from immigrant backgrounds and validity of the data collected from them and seeks to be a source of reference for institutional review boards (IRBs). Specific issues addressed include navigating IRBs, informed consent, recruitment and sampling, and translation of instruments and interviews. © 2013 Wiley Periodicals, Inc.